ECO FRIENDLY PRINTING ON COTTON FABRIC WITH SYNTHESIZED Azardirachta indica LEAF DYE EXTRACT - A. PADMA, PRATHYUSHA KANTHETI, KHATEEJA SULTHANA SHAIK AND (The Journal of Research, PJTSAU, 2019)
Azadirachta indica (commonly known as neem, nimtree and Indian lilac) belongs to the family Meliaceae. This tree is drought resistant and is native to the Indian subcontinent; it typically grows in tropical and semi-tropical regions. Its fruits, leaves and seeds have many medicinal and therapeutic values. In India, it is called as sacred tree and in villages serves as a pharmacy for many diseases. In the present study, natural dye was extracted from neem leaves through aqueous method which was used as colouring pigment in print paste for screen printing. Nanoparticles were prepared from neem leaves and these were mixed in the printing paste in different percentages to identify the difference in colour fastness and wash fastness along with colour improvement.